2016
DOI: 10.18552/ijpblhsc.v4i1.304
|View full text |Cite
|
Sign up to set email alerts
|

A Fair Exchange: The Reciprocal Relationship Between Universities and Clinical Placement Supervisors

Abstract: Clinical psychology training in the UK relies heavily upon supervised clinical practice placements. Placement supervisors have a significant responsibility for providing trainees with the learning experiences required for qualification. The role is demanding and whilst the university benefits greatly, it is less clear what supervisors receive in return. This is important when one considers how positive relationships and social action are influenced by reciprocity and a sense of belongingness. Despite its impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Traditionally, measures of clinical placement quality have been either unidisciplinary (e.g. Henzi et al 2006, Saarikoski et al 2008, Salamonson et al 2011, Walters et al 2011, or focused on a single stakeholder perspective: as examples, students (e.g., Dunn andBurnett 1995, Eley et al 2015), junior medical staff (e.g., Boor et al 2007), or supervisors (e.g., Sheils et al 2016). Cusick (2013) found that student learning outcomes were rarely considered in the measurement of placement quality or clinical learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, measures of clinical placement quality have been either unidisciplinary (e.g. Henzi et al 2006, Saarikoski et al 2008, Salamonson et al 2011, Walters et al 2011, or focused on a single stakeholder perspective: as examples, students (e.g., Dunn andBurnett 1995, Eley et al 2015), junior medical staff (e.g., Boor et al 2007), or supervisors (e.g., Sheils et al 2016). Cusick (2013) found that student learning outcomes were rarely considered in the measurement of placement quality or clinical learning outcomes.…”
Section: Introductionmentioning
confidence: 99%